Study on reinforced concrete beams strengthened externally using mengkuang leaves-epoxy composite plate - Foong, Yuen Kei (2016)
Synthetic fiber usage in reinforcing composite plate for variety of applications is a common practice on advance engineering structures such as automobiles and infrastructure in bridges and buildings. Study on using natural fiber as replacement to synthetic fiber was carried out for recent decades to investigate the potential use of natural fiber composite plate in strengthening of reinforced concrete (RC) structures as an alternative to synthetic fiber reinforced composite plate. A study has been carried out to investigate the potential use of mengkuang leaves-epoxy composite for the strengthening of reinforced concrete beams. Mengkuang leaves were treated sodium hydroxide (NaOH) in concentration of 2 %, 5 % and 8%, examined by using scanning electron microscope (SEM) and single fiber test, while composite plates were tested for flexural strength and used as external strengthening material on RC beams and tested under four-point bending test. Fiber volume fraction of 10 % - 40 % reinforced with epoxy were considered in this study. SEM micrographs showed that alkali treatment gives no significant effect on the leaves surfaces, the inner layer which consists of fiber was undefined. Experimental results showed that the tensile strength for untreated samples were found higher than treated samples and lower tensile strength was obtained as NaOH increases. Flexural strength of composites increases as fiber volume fraction increases from 10 % to 30 %. Fiber volume fraction of 30 % gives the most optimum results which improve the flexural strength about 96 % higher than the unreinforced epoxy plate. In terms of four-point bending test, the results showed that RC beams strengthened using mengkuang leaves-epoxy reinforced composite plate can sustained higher load capacity than the control beam and reduced the beam deflection. The increased in ultimate load varied from the range of 7 % to 13 % while the beam deflection reduced from 17 % to 38 %. In terms of crack pattern, vertical flexural cracks were found along the tension zone in the mid-span of the control beam. The control beams failed in bending. On the other hand, mengkuang leaves-epoxy reinforced composite plate has diverted the cracks that initially formed in the midspan of the beams to the edge of the plate causing the formation of diagonal shear cracks that propagated towards the point load of the beams. The mode of failure for mengkuang leaves-epoxy reinforced composite plate in strengthening RC beams were in bending with the peeling of composite plate. This signifies that mengkuang leaves-epoxy composite plate has potential to be used as an alternative external strengthening material to synthetic composite plate.